Efforts to Prevent the Transmission of Covid-19 Through a Clean and Healthy Lifestyle in Kalibagor Regency Housing Kalibagor Sub- District - Aris Fitriyani; Maisje Marlyn Kuhu (Universitas Malahayati Lampung, 2023)
ABSTRACT Data for March 31, 2020 showed that there were 1,528 confirmed cases of COVID-19 and 136 deaths in Indonesia. The COVID-19 mortality rate in Indonesia is 8.9%, this figure is the highest in Southeast Asia. This COVID-19 disease can be prevented by implementing a Clean and Healthy Lifestyle as a way to prevent COVID-19. The goal after socialization and education, is expected to be as an effort to prevent the transmission of COVID-19 through Clean and Healthy Living Behavior (PHBS) in Kalibagor Regency Housing, Kalibagor Village, Kalibagor District. The activities carried out were in the form of socializing the prevention of transmission of COVID-19 with PHBS with education through the WhatsApp (WA) group, installing posters and banners, distributing masks, and distributing simple hand washing facilities, distributing children's story books in the environment around the Kalibagor Regency Housing Complex, Kalibagor Village, District Calibagor and cooperate. There is an increase in knowledge and awareness about preventing the transmission of COVID-19 through Clean and Healthy Living Behavior (PHBS) at Kalibagor Regency Housing, Kalibagor Village, Kalibagor District. Keywords: Prevention of transmission of COVID-19, Clean and Healthy Lifestyle, Residents of Kalibagor Regency Housing